Is 12 months enough to reach function after athletes’ ACL reconstruction: a prospective longitudinal study (Clinics, 2022)
ContextAnterior Cruciate Ligament (ACL) injury is disabling in several sports because it causes knee instability and functional deficit. Usually, surgical treatments produce the best functional outcomes, however, sometimes they are not always able to fully restore stability and function.Objective: The objective of this study was to evaluate postural balance, muscle strength, and functional performance of young athletes with an ACL injury before and after ACL reconstruction.Design: This was a longitudinal observational prospective study.Method: 74 athletes, 60 men, and 14 women, aged between 16 and 45, divided into two groups: the Group-Lesion of ACL with 34 athletes (24.1 years) and the Group-Control with 40 athletes without ACL lesion (27.7 years old). All volunteers performed posturography, isokinetic dynamometry, and the Hop-Test. The ACL-Group was evaluated before and 12 months after the reconstruction and the control group was evaluated once.Results: The Postoperative ACL Group presented greater limb symmetry, 0.96 (± 0.12), than the preoperative ACL Group, 0.87 (± 0.17), p < 0.01 in the Hop-Test. In the posturography, the displacement area was smaller in the postoperative ACL Group, 19.85 (± 5.74), compared to the preoperative ACL Group, 24.20 (± 8.97), p < 0.01. In isokinetic dynamometry the torque peak was greater in the postoperative ACL Group, 0.91 (± 0.14), than in the preoperative ACL Group, 0.74 (± 0.15), p < 0.01.Conclusion: The functional outcomes increased in ACL reconstruction athletes after 12 months, but not at the same level as in the Control Group. The result indicates an incomplete functional recovery, adaptive changes in postural control after injury, reconstruction, and return to sport.